Business marketing : Connecting strategy, relationships, and learning - Dwyer, F. Robert; Tanner, John F. (New York McGraw-Hill/Iwin, 2006)
This text is targeted at the undergraduate Business Marketing course. It introduces the concepts of marketing to businesses and stresses the importance of building relationships with customers.
Includes bibliographical references and index
Keywords: Quản trị kinh doanh